Synthesis of biocompatible, BSA capped fluorescent CaCO3 pre-nucleation nanoclusters for cell imaging applications. Issue 26 (9th June 2020) - Sabbarwal, Shivesh; Dubey, Ashutosh Kumar; Pandey, Maneesha; Kumar, Manoj
Abstract : Novel photostable, multicolour fluorescent, highly biocompatible, water soluble, BSA capped pre-nucleation CaCO3 nanoclusters (FCPN) (∼1.3 nm) are developed using a facile biomineralization process. Abstract : Novel, photostable, multicolour fluorescent, highly biocompatible, water soluble, BSA capped pre-nucleation CaCO3 nanoclusters (FCPN) (∼1.3 nm) are developed using a facile biomineralization process. M. oleifera leaf extract and BSA protein are used as sources of ascorbic acid and capping agent, respectively. The developed FCPN shows fluorescence in the blue, green, and yellow/red region with an average life time of 1.05, 6.23 and 30.60 ns, respectively. The MALDI-MS measurements reveal that these nanoclusters are 16, 50, 73, 222 and 936 molecules big. These FCPN, when incubated (up to 7 days) with MG-63 cells, demonstrate an increase in cell viability percentage with time period as compared to their control samples. Furthermore, these incubated cells were investigated using confocal microscopy to estimate the FCPN diffusion penetration depth using CTCF analysis. It has been observed that blue and green emitting FCPN penetrated 6 μm, whereas red emitting FCPN traversed only 4 μm. The relative quantum yield (Rhodamine 6G = 0.92) of FCPN for green emission was found to be 0.0175 in water. The prepared nanoclusters displayed four months shelf-life. These FCPN were prepared using an environmentally benign, inexpensive, green synthetic route without using toxic reducing agents. Furthermore, the current report discusses the detailed results, obtained from X-ray photoelectron spectroscopy, MALDI-MS, Fourier transform infrared spectroscopy, UV-visible, fluorescence spectroscopy, lifetime measurements, electron microscopy, fluorescence microscopy and confocal microscopy.